Pengaruh Kepuasan Kerja, Komitmen Organisasi, dan Budaya Organisasi terhadap Organizational Citizenship Behavior di PDAM Tirta Taman Sari Kota Madiun - Marlinda Rofiqoh; Isharijadi Isharijadi; Farida Styaningrum (Universitas Merdeka Madiun, 2020)
Abstractâ€” This research aim to know influence of job satisfaction, organizational commitment, and organizational culture to organizational citizenship behaviour of PDAM Tirta Taman Sari Madiun City. This research is quantitative analytical research with primary data. These samples in this research is 104 regular employees. While used data collecting technique that is with questioner and documentation. The research instrument used was the Likert scale. The calculation data analysis technique uses Smart PLS, which includes descriptive statistical analysis, the outer model, inner model, and hypothesis testing by looking at the t-statistical value. The result showed job satisfaction, organizational commitment, and organizational culture positive and significant impact on organizational citizenship behavior.Â Keywordsâ€”: job satisfaction; organizational commitment; organizational culture; organizational citizenship behaviour.